The Role of Forum Kerukunan Umat Beragama (FKUB) for Religious Harmony and the Rights of Freedom of Religion or Belief (Forb) - Ahmad Faqih (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2021)
This study aims to describe the extent of the Forum of Religious Harmony’s (FKUB) roles and duties as a driving force for harmony and right protection for Freedom of Religion or Belief (Forb). To answer the problem, this paper formulates two questions: (1) how is the role of FKUB in protecting Forb rights and maintaining religious harmony and (2) does the formation of FKUB in protecting Forb as well as maintaining religious harmony in Indonesia work successfully or not. This study examines several regulations formulated regarding the right to freedom of religion or belief and the basic principles of human rights in Indonesia. This study found that although FKUB has been established based on the principles of justice and diversity of society in Indonesia, its programs tend to only focus on one issue such as licensing places of worship, while the issue of empowering religious community, fostering tolerance, and fighting radicalism are less appreciated.